Designing a ComicQu Application for VIII Graders’ Reading – Writing Assessment - Rahman, Nadya Septiani; Hermayawati, Hermayawati (LPPM Universitas Mercu Buana Yogyakarta, 2019)
This study aimed at producing media that contain the